A review of the challenges, glycaemic risks and self‐care for people with type 1 diabetes when consuming alcoholic beverages. (6th February 2020) - Charlton, Jacqui; Gill, Jan; Elliott, Lawrie; Whittaker, Anne; Farquharson, Barbara; Strachan, Mark
Abstract: Evidence‐based information for people with type 1 diabetes mellitus (T1DM) when consuming alcoholic beverages is sparse and simplistic. In clinical practice, erratic blood glucose levels with hypoglycaemia and hyperglycaemia are regularly observed, with episodes of severe hypoglycaemia being a potential risk. Preventative health behaviour strategies are often based on trial and error, with deliberately caused hyperglycaemia being a common tactic. Although important, there are no systematic reviews that synthesise the research evidence on the acute effects of alcohol on blood glucose and the impact in real‐life. We aimed to investigate the acute effect of alcoholic beverages on blood glucose, and to use appropriate evidence to recommend self‐care advice to help maintain safe glycaemic control in people with T1DM. A literature search from eight bibliographic databases was performed. Fifteen appropriate publications were identified. Most original research was performed in a laboratory environment and demonstrated inconsistencies in the effects of alcohol on blood glucose. Few studies were conducted in the real‐life environment, with advice from 'diabetes associations' focusing on abstinence rather than alcohol harm reduction strategies. In conclusion, key components to consider when designing future interventions include: the biochemical response to alcohol; the role of exogenous insulin; the presence and timing of carbohydrate foodstuffs in relation to alcohol; the impact of the constituents and amount of an alcoholic beverage consumed; and the effects of alcohol on cognition and behaviours.